The Influence of Parenting Styles on Children’s Character Development: A Gender-Based Analysis - Aminu, Nurmin; Aswat, Hijrawatil; Nurastuti, Nurastuti; Sinta, Dewi; Manaf, Abdul; Ahmad, Abdul Kadir (Jurnal Pendidikan Progresif, 2025)
The Influence of Parenting Styles on Children’s Character Development: A Gender-Based Analysis. Objectives: Character quality is one of the skills that children must have in the 21st century. The character formed in children is influenced by their parents' parenting, so the purpose of this study is to analyse the character of male and female based on parenting. Methods: The research approach used was quantitative with a survey type. The sample was 60 children from Halimombo and Bonatiro villages, Buton Regency, Southeast Sulawesi Province, Indonesia. The data collection instrument used a questionnaire containing 29 statement items to measure the characters of honesty, responsibility, discipline, religion, and hard work. The questionnaire met the valid and reliable criteria. The collected data were analysed using descriptive statistical analysis and network analysis. Findings: The findings of this study indicate that there is no significant difference (tvalue < 1.96 and Sig > 0.05) in the character of honesty, responsibility, discipline, religion, and hard work in male and female based on parental patterns. Honest character in male (JI, J5) and female (J1, J25) has a strong density and correlation. The character of responsibility in male (T15, T18) and female (T4, T24) has a strong density and correlation. Discipline characters in male (D20, D21) and female (D8, D21) have strong density and correlation. Religious characters in male (R6, R11) and female (R6, R29) have strong density and correlation. The character of hard work in male and female (K9, K28) has a strong density and correlation. Conclusion: Parenting is very important in the formation of children's character. Good parenting has a positive impact on the formation of children's character. So the factors of child character formation based on gender are very important for parents to know.Keywords: character, parenting, gender, parents, children.